Primary and secondary prevention of cerebral ischemia: joint guidelines of the German Society of Neurology (DGN) and German Stroke Society (DSG) - Diener, Hans-Christoph; Aichner, F.; Bode, C.; Böhm, M.; Eckstein, H.-H.; Einhäupl, K.; Endres, M.; Forsting, F.; Gesenhues, S.; Grond, M.; Haberl, R. L.; Hacke, Werner; et al. (Aktuelle Neurologie, 2010)
Classification of level of evidence: ↑↑ Efficacy and usefulness is well supported by multiple appropriate clinical studies (i.e. controlled randomized trials), either one or more metaanalyses or systematic reviews. ↑Efficacy and usefulness is supported by at least one appropriate clinical study (i.e. controlled randomized trial). ↓↓ Lack of efficacy is well supported by one or more appropriate clinical studies (i.e. controlled randomized trial), either one or more metaanalyses or systematic reviews. ↔ No study results exist to prove any benefit or harm. This can be due lack of appropriate studies, or several studies with controversial results.